1989
DOI: 10.1128/jb.171.11.6039-6042.1989
|View full text |Cite
|
Sign up to set email alerts
|

Purification and some properties of glutathione S-transferase from Escherichia coli B

Abstract: Glutathione S-transferase was purified approximately 2,300-fold from cell extracts of Escherichia coli B with a 7.5% activity yield. The molecular weight of the enzyme was 45,000, and the enzyme appeared to consist of two homogeneous subunits. The enzyme was almost specific to 1-chloro-2,4-dinitrobenzene (K,. 1.43 mM) and glutathione (K,,, 0.33 mM). The optimal pH and optimal temperature for activity were 7.0 and 50°C, respectively, and the enzyme was stable from pH 5 to 11. The activity of the enzyme for 1-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
5

Year Published

1990
1990
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 20 publications
1
33
0
5
Order By: Relevance
“…In the past, GST had been characterized in eukaryotes as a detoxifying enzyme. However, several recent reports concerning bacterial GSTs have appeared (1,13,24). It has been shown that GST plays a role in the assimilation of dichloromethane in Methylobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, GST had been characterized in eukaryotes as a detoxifying enzyme. However, several recent reports concerning bacterial GSTs have appeared (1,13,24). It has been shown that GST plays a role in the assimilation of dichloromethane in Methylobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…They are not quantitatively prominent proteins in the cell, judging from the purification factors reported (0.002 to 0.1%) (32,64,71). The presence of CDNB-active GST enzymes was associated with increased resistance of the bacterial host to several antibiotics (70,71).…”
Section: Yet More Versatility: Bacterial Gst Enzymesmentioning
confidence: 99%
“…The activity of the enzyme toward CDNB was significantly lower than the enzymes from mouse, corn and F. oxysporum (Lee et al, 1981;Mozer et al, 1983;Ando et al, 1988). On the other hand, it was similar to those of the enzymes from bacteria (Izuka et al, 1989;Nishida et al, 1994).…”
Section: Discussionmentioning
confidence: 91%
“…The theta-class GSTs purified from Arabidopsis thaliana and mouse liver exhibited selenium-independent glutathione peroxidase activity (Bartling et al, 1993;Hiratsuka et al, 1995). On the other hand, E. coli B GST showed neither selenium-dependent nor independent glutathione peroxidase activity, indicating that the properties of catalytic sites between eukaryote and prokaryote enzymes may be different (Izuka et al, 1989). The molecular cloning of the GST gene of Lactuca sativa is now in progress in order to elucidate the difference in the molecular structure between the Lactuca sativa GST and enzymes of other sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation